Hubungan Kompetensi Sosiolinguistik dengan Keterampilan Berbicara Bahasa Indonesia pada Mahasiswa - Indramini Indramini (Prodi PGSD Unsultra, 2026)
This study aimed to determine the relationship between sociolinguistic competence and Indonesian speaking skills among students of the Indonesian Language Education Study Program at Universitas Muhammadiyah Makassar. The study employed a quantitative approach using a correlational research design. The population consisted of 250 students, while 100 students were selected as the sample through purposive sampling. The research instruments included a sociolinguistic competence questionnaire and a speaking skills performance test. Data were analyzed using descriptive statistics, normality tests, linearity tests, Pearson Product Moment correlation, and coefficient of determination with the assistance of SPSS version 26. The results revealed that students’ sociolinguistic competence was categorized as high, with a mean score of 82.45. A total of 65% of students were classified in the high category, 28% in the moderate category, and 7% in the low category. Meanwhile, students’ speaking skills were categorized as good, with a mean score of 80.12. Approximately 61% of students were in the good category, 31% in the moderate category, and 8% in the low category. The normality test indicated that the data were normally distributed, while the linearity test confirmed a linear relationship between the variables. Pearson Product Moment correlation analysis produced a correlation coefficient (r) of 0.684 with a significance value of 0.000 (p < 0.05). These findings indicate a positive and significant relationship between sociolinguistic competence and speaking skills. Furthermore, the coefficient of determination showed that sociolinguistic competence contributed 46.8% to students’ speaking skills, while the remaining 53.2% was influenced by other factors not examined in this study. Therefore, sociolinguistic competence can be considered an important factor in improving students’ speaking skills.